(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
There had always been the need to raise the financial position of the local bodies. Various commissions and committees formed by the central as well as state governments like the Rural-Urban Relationship Committee,1966, the High-Power Committee on Municipal Finances and Financial Administration, Government of Andhra Pradesh,1971, the Committee on Budgetary Reforms in Municipal Administration,1974, the Asoka Mehta Committee on Panchayati Raj,1978, the National Commission on Urbanisation,1988, etc., have been suggesting the constitution of the State Finance Commissions with a view to take measures to make these institutions of local governance financially strong and viable to cope with the pressures from the various stake holders at local level to perform better and to enhance the quality and the quantity of the services delivered.